Pelaksanaan Hukuman Cambuk di Tapaktuan Menurut Perspektif Fiqih Jinayah (Studi Komparatif) - Mihfa Rizkiya (Hikmah, 2015)
This paper discusses the implementation of caning in Tapaktuan. The author would like to examine how the application of the principles of the Islamic caning, why there is a fundamental difference between fiqh jinayah caning according to the applied caning in Aceh, which based on Islamic law, and what are the obstacles that impede the passage of the execution of this whip for criminals in Tapaktuan. In this study the authors wanted to explore how the principles of caning under Islamic law, how the application hukuman cambuk in Tapaktuan, what is the reason for the differences in the application of flogging jinayah Tapaktuan with principles, and how the public perception Tapaktuan with the caning. The research conducted in this jurnal is empirical legal research or research nondoktrinal known. Said, because this study examines the law and has been applied in the field by people in Tapaktuan South Aceh. This research is descriptive method of analysis is to describe the object of research based on data and facts on the ground. the means used to collect the data is the qualitative method is an approach that is not done by using formulas or statistical symbols, but directly collect data found from the research.